Rebel [videorecording (DVD)] : Loreta Velazquez, secret soldier of the American Civil War - Carter, Maria Agui; Dias, Romi; Carter, Isabel (PBS, 2013)
In 1861, at the outbreak of the American Civil War, a teenager from New Orleans headed to the front lines. Under the alias Harry T. Buford, he fought at First Bull Run, was wounded at Shiloh, and served as a Confederate spy. By 1863, Buford was working for the Union. But Buford harbored a secret: he was really Loreta Velazquez, a Cuban immigrant from New Orleans.